Association of Oral Health-Related Quality of Life with the Longevity of ART-Restorations in Children - Juana Rosmeri Salas-Huamani; Karina Guedes de Sousa; Gabriellen Fernanda Gomes; Amanda Fernandes Silva; Thalita Lucas Brum Moreira da Silva; Fabíola Galbiatti de Carvalho; Renata Andrea Salvitti de Sá Rocha; Taís de Souza Barbosa (Association of Support to Oral Health Research (APESB), 2023)
Objective: To evaluate the association of oral health-related quality of life (OHRQoL) with the longevity of ART-restorations in children after 18 months. Material and Methods: A longitudinal clinical study with 62 six- to seven-year-old children, both genders, 31 of whom underwent four weeks of oral health education strategy (OHES) followed by ART (GOHES+ART) and the others only ART (GART). The Brazilian short-version of the Child Perceptions Questionnaire (16-CPQ8-10) was used to evaluate the OHRQoL and the perception of change in oral health was assessed by a single question. Data was analyzed using Mann-Whitney, Wilcoxon and Friedman's tests. Results: After 18 months, GOHES+ART reported a greater impairment on OHRQoL, mainly in oral symptoms domain (p<0.05). In this period, greater impairment of oral symptoms was reported in children with failed restorations and with treatment considered to have a minor failure (p<0.05). In inter-group analysis, the GOHES+ART, with 2 to 4 restorations, Class I, of small size, located in the upper arch and with a smaller failure, reported more oral symptoms than the GART. Conclusion: In the long-term, children submitted to OHES followed by ART reported more oral symptoms. Factors such as number, class, size and location of the restorations need to be considered for the implementation of an efficient and effective oral health program, as well as for greater longevity of ART-restorations.